The problems of teaching Ukrainian as a state language in Transcarpathia - Csernicskó István; Черничко Степан; Csernicsko Istvan (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-Grafika, 2015)
Abstract. The territory of the administration unit that we call Transcarpathia today existed neither as a geographical, nor as a geopolitical entity. Throughout the 20th century it belonged to several countries (Csernicskó & Ferenc, 2014). The state language has changed six times during the 20th century and accordingly changed the compulsory language taught in the schools of the region. The compulsory state language role was fullled by the Hungarian, Czechoslovakian, Russian and Ukrainian.
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00000939
https://www.kmf.uz.ua/hun114/images/konyvek/modern-trends_11_17.pdf
Keywords: Ukrainian language; Transcarpathia; teaching